Mineralocorticoid receptor antagonists as diuretics: Can congestive heart failure learn from liver failure? - Masoumi, Amirali (Heart Fail Rev, 2015)
Despite significant improvements in diagnosis, understanding the pathophysiology and management of the patients with acute decompensated heart failure (ADHF), diuretic resistance, yet to be clearly defined, is a major hurdle. Secondary hyperaldosteronism is a pivotal factor in pathogenesis of sodium retention, refractory congestion in heart failure (HF) as well as diuretic resistance. In patients with decompensated cirrhosis who suffer from ascites, similar pathophysiological complications have been recognized. Administration of natriuretic doses of mineralocorticoid receptor antagonists (MRAs) has been well established in management of cirrhotic patients. However, this strategy in patients with ADHF has not been well studied. This article will discuss the potential use of natriuretic doses of MRAs to overcome the secondary hyperaldosteronism as an alternative diuretic regimen in patients with HF.